Efficacy and tolerability of pharmacotherapy for smoking cessation in adults with serious mental illness: a systematic review and network meta‐analysis. (19th January 2016) - Roberts, Emmert; Eden Evins, A.; McNeill, Ann; Robson, Debbie
Abstract: Background and Aims: To assess the efficacy and tolerability of adjunctive pharmacotherapy for smoking cessation in adults with serious mental illness (SMI) by means of a systematic review and network meta‐analysis. Method: We searched Embase, Medline, PsychINFO and the Cochrane Central Register of Controlled Trials from database inception to 1 December 2014 for randomized controlled trials (RCTs) published in English. We included all studies of smokers with SMI (including schizophrenia, schizoaffective disorder, bipolar disorder, delusional disorder and depressive psychoses) who were motivated to quit smoking. Pharmacotherapies included nicotine replacement therapy (NRT), bupropion and varenicline delivered as monotherapy or in combination compared with each other or placebo. The efficacy outcome was self‐reported sustained smoking cessation, verified biochemically at the longest reported time‐point. The tolerability outcome was number of patients discontinuing the trial due to any adverse event. Results: Seventeen study reports were included, which represented 14 individual RCTs. No trials were found in patients with depressive psychoses, delusional disorder or that compared NRT monotherapy with placebo. A total of 356 and 423 participants were included in the efficacy and tolerability analyses, respectively. From the network meta‐analysis, both bupropion and varenicline were more effective than placebo [odds ratio (OR) = 4.51, 95% credible interval (CrI) = 1.45–14.04 and OR = 5.17, 95% CrI = 1.78–15.06, respectively]. Data were insensitive to an assessment of varenicline versus bupropion (OR = 1.15, 95% CrI = 0.24–5.45). There were no significant differences in tolerability. All outcomes were rated by GRADE criteria as very low quality. Conclusions: The limited evidence available to date suggests that bupropion and varenicline are effective and tolerable for smoking cessation in adults with serious mental illnesses.